Genetic interaction implicates iRhom2 in the regulation of EGF receptor signalling in mice - Siggs, O; Grieve, A; Xu, H; Bambrough, P; Christova, Y; Freeman, M (Company of Biologists, 2014)
iRhoms are closely related to rhomboid intramembrane proteases but lack catalytic activity. In mammals iRhoms are known to regulate the trafficking of TACE, the protease that cleaves the membrane bound inflammatory cytokine TNF. We have mapped a spontaneously occurring mouse mutation with a loss of hair phenotype, curly bare (cub), to the Rhbdf2 locus, which encodes the iRhom2 protein. The cub deletion removes the first 268 amino acids of the iRhom2 protein but is not a loss of function. We have also identified a previously reported suppressor of cub, called Mcub (modifier of curly bare), and find it to be a loss of function allele of the amphiregulin gene (Areg). Amphiregulin is an activating ligand of the epidermal growth factor receptor (EGFR) that, like TNF, is released by TACE. Our results therefore imply a regulatory link between iRhoms and EGFR signalling in mammals. We have tested the model that the cub mutation leads to iRhom2 hyperactivity and consequently excess TACE processing of amphiregulin and elevated EGFR signalling. Our results do not support this hypothesis: we find that, compared to wild-type cells, cub mutant embryonic fibroblasts release less amphiregulin, and that the cub mutant form of iRhom2 is less able than wild type to bind to TACE and promote its maturation.